EFEKTIFITAS TINDAKAN EPISOTOMY DALAM MEMPERCEPAT PROSES PERSALINAN (Politeknik Kesehatan Kemenkes Bandung, 2022)
Perineal rupture can have long and short term effects on the mother. Bleeding is a short-term impact of perineal rupture that occurs with every vaginal delivery. Historically, episiotomy was believed to reduce perineal injury and anal sphincter rupture by controlling the direction and extent of tissue damage. An episiotomy tear is considered easier to repair than a spontaneous perineal tear and it is thought that an episiotomy can prevent perineal rupture. This evidence based case report aims to determine the effectiveness of episiotomy in accelerating the labor process. The search for articles on the effectiveness of episiotomy in speeding up the labor process was carried out in Pubmed and Google Scholar. Obtained 1 article randomized-controlled trial by mario, et al. which meet the inclusion and exclusion criteria and have been previously screened, then critically reviewed. After critically reviewing the research by Mario, et al. declared valid, important, and applicable to the patient. Episiotomy action selectively (not routinely done) and according to procedure provides benefits and speeds up the delivery process. In addition, there was also 1 literature review article by Mario, et al. In this literature review, it was found that an episiotomy was performed when the patient had a higher risk of laceration, the episiotomy was performed at a more open angle (>40°) and earlier in the expulsive period. With this technique, this technique is effective in speeding up the labor process by minimizing the higher risk of laceration .